UNDERSTANDING EMOTION AS A COMMUNICATION BARRIER AMONG EXECUTIVES IN CORPORATE ORGANIZATION TOWARDS EFFECTIVE COMMUNICATION - Muhammad Firdaus Daud; Ahmad Syakir Salman Salleh @ Abdul Latif; Ku Nurul Atiqah Ku Ahamad; Muhammad Azril Izuan Ramlan; Mohamed Shafiq Mohamed Ayub, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
This research is conducted using qualitative method in understanding the deeper meaning of emotion as a communication barrier. A conceptual framework has been developed to understand these communication barriers on a deeper level and they are categorized into four dimensions which are, 1) socialization between employees, 2) competition between employees, 3) collaboration between employees, 4) proper communication in resolving conflict. To achieve these objectives, a total of 5 informants have been interviewed using in-depth interview method. The informants are chosen among the executives working in Sime Darby Bhd as the organization is a conglomerate consisting of multiracial employees and they are selected using purposive sampling. The location of this study is the headquarter of Sime Darby Bhd, situated in Jalan Raja Laut, Kuala Lumpur. The findings of this current research conclude that the factors such as avoidance, collaboration and compromise as laid out by the past researcher could not be categorized as the factor that cause communication barriers in Sime Darby Bhd.